Unleashing potential: The impact of supervisor trust on organizational citizenship and job performance - Niwes, Apichaya; Kulachai, Waiphot; Wannarak, Junphen; Homyamyen, Patipol (Edelweiss Applied Science and Technology, 2024)
This study investigates the complex interplay among trust in supervisors (TIS), organizational citizenship behaviours (OCB), and work performance (WP) in the workplace, aiming to determine whether trust in supervisors directly influences job performance or if this relationship is mediated by organizational citizenship behaviours. Using Structural Equation Modelling (SEM) via Smart PLS, data were collected from 215 officials through a structured questionnaire, capturing perspectives on trust in supervisors, engagement in OCB, and self-reported job performance. The results reveal that while trust in supervisors significantly fosters OCB, its direct impact on job performance is not statistically significant; however, OCB significantly enhances job performance, emphasizing its crucial mediating role. These findings highlight the importance of trust in supervisors in cultivating organizational citizenship behaviours that indirectly elevate job performance. Organizations should focus on trust-building initiatives to promote a supportive environment that encourages proactive engagement and performance excellence among employees, while future research should explore longitudinal data and diverse samples to further validate these findings.